Inhibition of T-cell responsiveness during experimental infections with Trypanosoma brucei: active involvement of endogenous gamma interferon. - Darji, A (1993)
Lymph node cells (LNC) from mice infected with Trypanosoma brucei contain macrophage-like cells that inhibit interleukin-2 receptor (IL-2R) expression (M. Sileghem, A. Darji, R. Hamers, M. Van De Winkel, and P. De Baetselier, Eur. J. Immunol. 19:829-835, 1989). Evidence that gamma interferon (IFN-gamma) is actively involved in (i) the inhibition of IL-2R expression and (ii) the generation of suppressive cells during infections with T. brucei is presented. First, despite an impaired T-cell mitogenic response, LNC from infected mice are hyperresponsive for IFN-gamma production. Second, addition of neutralizing anti-IFN-gamma antibodies to cocultures of normal LNC and suppressive LNC populations reduces the level of suppression and restores the level of IL-2R expression. Third, administration of anti-IFN-gamma to T. brucei-infected animals increases the blastogenic response and reduces the suppressive activity of LNC.